2023
DOI: 10.1186/s12957-023-02964-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic D3 lymph node dissection with left colic artery and first sigmoid artery preservation in rectal cancer

Abstract: Background D3 lymph node dissection with left colic artery (LCA) preservation in rectal cancer surgery seems to have little effect on reducing postoperative anastomotic leakage. So we first propose D3 lymph node dissection with LCA and first sigmoid artery (SA) preservation. This novel procedure deserves further study. Methods Rectal cancer patients who underwent laparoscopic D3 lymph node dissection with LCA preservation or with LCA and first SA p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…What needs to be stated is that although this is a good technique for rectal cancer patients it is not a universal procedure for all patients. As we have mentioned before [12], sometimes preservation of first the SA may lead to anastomotic tension, and even to anastomotic failure. If the tension is identified after anastomosis, the patient would accept additional mobilization or even complete mobilization of the splenic flexure, so sacrificing the preserved LCA and/or SA is our last resort.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…What needs to be stated is that although this is a good technique for rectal cancer patients it is not a universal procedure for all patients. As we have mentioned before [12], sometimes preservation of first the SA may lead to anastomotic tension, and even to anastomotic failure. If the tension is identified after anastomosis, the patient would accept additional mobilization or even complete mobilization of the splenic flexure, so sacrificing the preserved LCA and/or SA is our last resort.…”
mentioning
confidence: 83%
“…Although preservation of the left colic artery (LCA) has become more and more popular in rectal cancer surgery, it seems to have a limited role in preventing anastomotic leakage compared with nonpreservation of the LCA [6][7][8][9]. In recent years, we have focused on the surgical technique of D3 lymph node dissection with preservation of more branches of the IMA in rectal cancer surgery, and first proposed D3 lymph node dissection with preservation of the LCA and first sigmoid artery (SA) in rectal cancer surgery [10][11][12]. Our previous study found that preservation of the LCA and the first SA may be more important than preservation of the LCA alone [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation